Batman film series: friedrich nietzsche’s beyond good and evil in hollywood superhero films / Mohamad Faez Yahya - Yahya, Mohamad Faez (Faculty of Film, Theatre and Animation, 2015)
This research focuses on the philosophy of Friedrich Nietzsche’s Beyond Good and Evil which can be found in the Hollywood Superhero films. This philosophy summarizes on the complex of characters and characteristics of human beings in terms of morality. The problem statement regarding this research is the audience point of view on good versus evil as the main theme in this film genre. Furthermore, this research focuses on a selection of Batman film series that range from Joel Schumacher 1990s Batman film series to the latest Christopher Nolan’s Batman: The Dark Knight film series. So in this research, the philosophy of Beyond Good and Evil are place in various Batman film characters from heroes like Batman and Robin to villains like The Joker and Mr. Freeze. This research discovers that in some circumstances the characteristics of heroes do possess immoral characteristics and on the other hand the villains show an act of goodness. In addition, there are contributions and references on the theatre play The Birth of Tragedy that was written by Friedrich Nietzsche.